LubriShieldTM—A permanent urinary catheter coating that prevents uropathogen biofilm formation in vitro independent of host protein conditioning - Ana I. Romero; Serhiy Surkov; Per Wirsén; Graeme Brookes; Linda Bergström; Jan Tejbrant; Elena Dhamo; Sandra Wilks; Catherine Bryant; Jan Andersson (PLoS ONE, 2025)
Catheter-associated urinary tract infection is one of the most common healthcare-associated infections, with biofilm formation playing a key role in its pathogenesis. Indwelling medical devices introduce ideal pathways inside the body for pathogens and feature surfaces conducive to biofilm development, often leading to severe clinical infections recalcitrant to antimicrobials. When bacteria and fungi switch to biofilm mode of growth, they produce a matrix in the form of extracellular polymeric substances (EPS). This creates a unique environment for growing virulent colonisers and persisting cells while forming a shielding barrier against immune system attacks, antimicrobial agents and mechanical removal by fluid shear forces. To address this challenge, LubriShield TM – a novel permanent coating – was invented and evenly applied to both internal and external surfaces of indwelling urinary Foley catheters. Without releasing active substances, it effectively prevented pathogens from producing biofilm. The superhydrophilic coating, incorporating a proprietary anti-fouling ligand, significantly inhibited colonising uropathogens from forming biofilm for up to 14 days in artificial urine medium without microbial killing (up to 99% reduction, P < 0.001 ). In a glass bladder flow model, LubriShield TM still significantly reduced biofilm formation by 83 % (P < 0.0001) . Importantly, LubriShield™ maintained its antibiofilm efficacy even after conditioning with fibrinogen, a host-derived protein known to promote bacterial attachment ( P = 0.007 ). RNA-seq analysis revealed significant downregulation of genes associated with microbial EPS formation on the coated surfaces. Additionally, microorganisms adhering to LubriShield TM coated catheters showed a 78% increased susceptibility to antibiotics compared to those on uncoated catheters ( P = 0.004 ).